Pengaruh Pendapatan Asli Daerah, Dana Bagi Hasil dan Belanja Modal terhadap Kemandirian Keuangan pada Pemerintah Daerah Kabupaten/Kota di Provinsi Kalimantan Timur Tahun 2019-2023 - Evi Zunnia; Sri Hartaty; Eka Jumarni Fithri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine the influence of local revenue, profit-sharing funds, and capital expenditure on financial independence in Regency/City Regional Governments in East Kalimantan Province. The data used in this study is secondary data with data obtained through the official website of the Central EPPID of the Audit Board of the Republic of Indonesia (BPK RI) in 2019-2023. This type of research is a quantitative research. The population that is the focus of this study includes all Regional Governments, consisting of 9 Regencies/Cities in East Kalimantan Province with a total sample of 45 in this study. The sample determination in this study used the